2011
DOI: 10.1007/s12013-011-9225-1
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Analysis of Intra-Abdominal Hemorrhage After Reduced-Size Liver Transplantation in Rat

Abstract: In this study, we analyzed causes of abdominal hemorrhage after reduced-size liver transplantation in rat. Healthy SD rats (weight range of 260-280 g) underwent liver transplantation, the donors were female and the recipients were male rats. The recipients were, on average, by <10 g heavier than the donors. All operations on donor rats were performed by the same person using unaided eyesight. Operations on recipient rats were performed by two persons using unaided eyesight. About 270 rats received reduced-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…before liver harvest [54,55,56,57], or at the back table [37,58,59]. The disadvantage of in situ resection via the mass ligation technique is the higher risk of complications caused by vessel deformation and consequential hepatic congestion; however, bleeding can be better recognized and treated when in situ resection is performed [60,61,62]. In addition, Schemmer et al [63] showed positive effects of reduced in situ surgical manipulations of the liver graft on survival in rat OLT, due to the diminished activation of Kupffer cells with the no-touch technique.…”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…before liver harvest [54,55,56,57], or at the back table [37,58,59]. The disadvantage of in situ resection via the mass ligation technique is the higher risk of complications caused by vessel deformation and consequential hepatic congestion; however, bleeding can be better recognized and treated when in situ resection is performed [60,61,62]. In addition, Schemmer et al [63] showed positive effects of reduced in situ surgical manipulations of the liver graft on survival in rat OLT, due to the diminished activation of Kupffer cells with the no-touch technique.…”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%
“…cefuroxime, cefazolin) [107] - should be considered during the early postoperative days [37,56,62,67,69,70,84,106,108,109]. As we also recommend in our publication guide attached to the present review (table 8), the use of medications (anesthetics, fluid, analgesics, antibiotics, etc.)…”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%